1981
DOI: 10.2527/jas1981.532434x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mating on the Luteinizing Hormone Surge in the Pig

Abstract: Twenty-eight cannulated crossbred gilts were assigned to one of four treatments: natural mating, artificial insemination (AI, whole semen), AI (seminal plasma) or control (nonmated). Blood samples were collected four times daily (0800, 1200, 1600 and 2000 hr) on the day before standing estrus, the day of the onset of standing estrus and the first day after the onset of standing estrus. Thereafter, blood samples were collected once daily (1200 hr) until 15 days postestrus. Analysis of luteinizing hormone (LH) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Natural mating shortens the interval between the onset of oestrus and ovula¬ tion in gilts (Pitkjanen, 1958;Signoret et al, 1972). This has been explained by the stimulatory effect of copulation (Ziecik et al, 1981;Kirsch et al, 1985) and by specific components of boar seminal plasma (Seglin'sh and Brutgans, 1981;Claus, 1989;Weitze et al, 1990). Previous studies that used the single uterine horn infusion technique with the contralateral uterine horn as the untreated control horn (Mariensee model, Jungblut et al, 1991) and sonographic monitoring of ovaries showed that infusion of seminal plasma at the onset of oestrus provoked ovulation in the ipsilateral ovary of the treated horn 10.7 h earlier than in the contralateral ovary.…”
Section: Introductionmentioning
confidence: 99%
“…Natural mating shortens the interval between the onset of oestrus and ovula¬ tion in gilts (Pitkjanen, 1958;Signoret et al, 1972). This has been explained by the stimulatory effect of copulation (Ziecik et al, 1981;Kirsch et al, 1985) and by specific components of boar seminal plasma (Seglin'sh and Brutgans, 1981;Claus, 1989;Weitze et al, 1990). Previous studies that used the single uterine horn infusion technique with the contralateral uterine horn as the untreated control horn (Mariensee model, Jungblut et al, 1991) and sonographic monitoring of ovaries showed that infusion of seminal plasma at the onset of oestrus provoked ovulation in the ipsilateral ovary of the treated horn 10.7 h earlier than in the contralateral ovary.…”
Section: Introductionmentioning
confidence: 99%
“…These results might be explained in part by the research of Randel et al (1973), who reported that cervical and clitoral stimulation caused an earlier preovulatory LH surge and ovulation in cattle. Also, Ziecik et at. (1981) suggested that natural mating may prolong the LH surge in the pig.…”
Section: Introductionmentioning
confidence: 93%
“…Accepted January 6, 1985 as pigs. Signoret et al (1972) and Ziecik et al (1981) reported that copulation reduced the duration of ovulation in the pig. These results might be explained in part by the research of Randel et al (1973), who reported that cervical and clitoral stimulation caused an earlier preovulatory LH surge and ovulation in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…But before even mentioning any quick fix, like adding estradiol to the suspended semen, one should step back and ask why we are confronted so quickly with an aging oocyte. Evidence has been accumulating over several decades that some ungulates, especially sheep, pig and cattle are facultative induced ovulators: mating during the first half day of standing heat accelerates the occurrence of the preovulatory LH peak and of ovulation(s) (Signoret et al 1972;Jochle 1973;Jlichle 1975;Ziecik et al 1981). As with induced ovulators, this allows for a synchronization of the chain of events involving male and female gametes, designed to guarantee a high level of fertilization and of pregnancies.…”
mentioning
confidence: 99%